The universe and beyond - Dickinson, Terence (Firefly Books, 2010)
A factual, up-to-date guide to the universe, written in accessible language and illustrated with the latest images from space probes and the largest observatories on Earth. Covers most major topics in modern astronomy without delving into them at textbook depth, but doesn't skimp on detail. Focuses on areas about which people most often ask questions